PERTUMBUHAN BIBIT KAKAO (Theobroma cacao. L) DI MEDIA TANAM GAMBUT YANG DIBERI TANAH MINERAL DAN ZEOLIT” - Ahdi Romadoni; Ida Nursanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Peat soil has a very low load-bearing capacity. Peat dries out non-reversibly, contains very low base cations and very high acid cations, very high organic C-C and very low nutrient levels. The addition of mineral soil to peat planting media will reduce the organic acids produced during the decomposition process. Zeolite in soil can improve soil conditions (physical, chemical and biological soil). This research aims to find out. The research aims to study the growth of cocoa seedlings when given mineral soil and zeolite in peat soil media. This research uses a Completely Randomized Design (RAL) with 2 factors. The first factor is the provision of ultisol soil (U) with 4 levels, namely: U0 = without application of ultisol soil, U1 = ultisol soil 15% by weight of the planting medium, U2 = ultisol soil 20% by weight of the planting medium, U3 = ultisol soil 25% by weight of the planting medium. second is Zeolite (Z) with 3 levels, namely: Z0 = without zeolite, Z1 = zeolite 100 g, Z2 = 200 g. Data were analyzed using analysis of variance, followed by Duncan's Multiple Range Test (DNMRT) at the α level of 5%. Research Results shows that the application of zeolite to peat media can significantly influence the growth of cocoa plants, especially the stem diameter.